(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Alexander V. Dzyuba (Rostov-on-Don, Russian Federation) This article provides cognitive-pragmatic analysis of wordplay used in Spanish advertising slogans to promote banks & credit agencies. Because of the Great Recession, Spanish banks are trying to win back the clients creating advertisements that show their focus on future and trying to form a special, close bond with a customer. One example of such bond-making, appearing before the financial crisis and nowadays, is the use of puns. The research shows that copywriters tend to use lexical and phrasal ambiguities as wordplay devices 76 % of the total amount of slogans). Almost mandatory requirement is to exploit the polysemy of words like fortuna (fortune), obligaci΄n (obligation / bond) or efectivo (effective / cash), which possess a special “financial” meaning, besides its other, ordinary sense. The most frequent polysemic words exploited in slogans are: inter΄s (interest), cuenta (account), cr΄dito (credit) & corriente (current / ordinary). Two meanings clash with each other and the addressee has to choose more relevant (salient) meaning or keep in mind both meanings to interpret the text right. This kind of puns helps to provide positive attitude towards banks and shows their creativity. Other less popular wordplay devices used in Spanish bank advertising are: deliberate set-phrase modification, paronomasia and chiasmus. The use of wordplay helps to make the slogan more concise and to entertain the addressee with a “puzzle” which he or she must resolve. The addressee gets rewarded for solving this puzzle with pleasure. Key words: wordplay, puns, polysemy, advertising, Spanish language, lexical ambiguity, banks. DOI 10.23683/1995-0640-2018-1-117-124